Study of Impact of Socio-Economic Condition of Patients on Rhinosporidiosis in a Tertiary Level Hospital of Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2016)
Background: Rhinosporidiosis has been known for over a hundred years since its first description in Argentina. It is a chronic granulomatous,non contagious infective condition characterized by a production of nasal polyps and other manifestation of nasal hyperplasia, with frequent recurrence after surgery. The objective of this present study was Impact of Socio-economic condition of patients on Rhinosporidiosis.Methods: 34 number of patients were included in this study with symptomatic Rhinosporidiosis.The main outcome of study were age, sex, socioeconomic status, Occupation, bathing habit and living area of patients.Results: The study showed that 61.76 percent of patients were in the age group of 6-20 years. The mean age of 20.62 (SD±13.87) years. Most of the Rhinospridiosis patiets were from lower economic class 24(70.59%) followed by middle class 9(26.47%) and 1(2.94%) patients were upper class of socioeconomic status.Student was the most common occupation of Rhinosporidiosis 17(50%) followed by farmer 7(20.59%). Most of the Rhinosporidiosis patients 31(91.18%) were taking bath in pond where cattle also take bath.Conclusion: Rhinosporidiosis are very common in male and frequent age incidence are 6-20 years. Most of the Rhinospridiosis patient were from lower economic class and most of the Rhinosporidiosis patient were taking bath in pond where cattle also take bath.Chatt  Shi Hosp Med Coll J; Vol.15 (1); Jan 2016; Page 12-16